Challenges and policy implications of long-term changes in mass absorption cross-section derived from equivalent black carbon and elemental carbon measurements in London and south-east England in 2014–2019. Issue 12 (30th November 2021) - Ciupek, Krzysztof; Quincey, Paul; Green, David C.; Butterfield, David; Fuller, Gary W.
Abstract : This paper concludes that mass absorption cross-section (MAC) values in London, UK have changed over time. It provides possible explanations and highlights implications for the interpretation of long-term trends. Abstract : Determining the concentration of carbonaceous particles in ambient air is important for climate modelling, source attribution and air quality management. This study presents the difficulties associated with the interpretation of apparent long-term changes in the mass absorption cross section (MAC) of carbonaceous particles in London and south-east England based on equivalent black carbon (eBC) and elemental carbon (EC) measurements between 2014 and 2019. Although these two measurement techniques were used to determine the concentration of carbonaceous aerosols, the concentrations of eBC and EC changed at different rates at all sites, and exhibited different long-term trends. eBC measurements obtained using aethalometer instruments for traffic and urban background sites demonstrated consistent trends, showing decreases in concentrations of up to −12.5% y −1 . The EC concentrations showed no change at the urban background location, a similar change to eBC at the traffic site and a significant upward trend of +10% y −1 was observed at the rural site. Despite these differences, the trends in the MAC values decreased at all sites in a similar way, with rates of change from −5.5% y −1 to −10.1% y −1 . The different trends and magnitudes of change for the eBC and EC concentrations could lead to uncertainty in quantifying the efficacy of intervention measures and to different conclusions for policy making. This paper provides possible explanations of the observed decrease in MAC values over time.